2010
DOI: 10.1007/s11745-010-3456-6
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterol Ester Constituents Affect Micellar Cholesterol Solubility in Model Bile

Abstract: Plant sterols and stanols (phytosterols) and their esters are nutraceuticals that lower LDL cholesterol, but the mechanisms of action are not fully understood. We hypothesized that intact esters and simulated hydrolysis products of esters (phytosterols and fatty acids in equal ratios) would differentially affect the solubility of cholesterol in model bile mixed micelles in vitro. Sodium salts of glycine- and taurine-conjugated bile acids were sonicated with phosphatidylcholine and either sterol esters or combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 28 publications
3
36
1
1
Order By: Relevance
“…Four different phytosterols decreased cholesterol solubility to a very similar extent. Stigmasterol was, by a small margin, the most potent of the four, decreasing the concentration of micellar cholesterol and total solubilized sterols [32]. In this study, stigmasterol was not found in USF of PFAD.…”
Section: The Effect Of Usf On Lipid Profile Improvementcontrasting
confidence: 48%
“…Four different phytosterols decreased cholesterol solubility to a very similar extent. Stigmasterol was, by a small margin, the most potent of the four, decreasing the concentration of micellar cholesterol and total solubilized sterols [32]. In this study, stigmasterol was not found in USF of PFAD.…”
Section: The Effect Of Usf On Lipid Profile Improvementcontrasting
confidence: 48%
“…However, because intact phytosterol esters do not incorporate into micelles or affect cholesterol solubility within mixed micelles in vitro [34], unhydrolyzed phytosterol esters may affect cholesterol absorption independent of micelles by creating a lipid phase in which cholesterol becomes trapped. Indirect evidence for this can be inferred by decreased cholesterol absorption in triglyceride lipase knockout mice fed a high-cholesterol, high-fat diet [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, plant sterols and their esters offer an opportunity to modulate cholesterol metabolism in hamsters (19). These compounds reduce cholesterol absorption in the intestine by a displacement of cholesterol by the plant sterol in intestinal micelles, by cocrystallization between plant sterols and cholesterol leading to the formation of insoluble crystals, and by impeding cholesterol hydrolysis by lipases and cholesterol esterases (20)(21)(22)(23)(24)(25)(26). The chemical processes by which plant sterols exert their actions have been extensively studied in vitro and do not require the participation of intestinal bacteria.…”
mentioning
confidence: 99%